Proposal of geoeducational actions for the diffusion and valorization of geodiversity and geopatrimony - Silva, José Francisco de Araújo; Aquino, Cláudia Maria Sabóia de (Geosaberes; Vol 9 No 17 (2018): Jan - AprDO - 10.26895/geosaberes.v9i17.617, 2017)
Despite the enormous geodiversity that Brazil has, there is still a lack of knowledge of this, especially in the school environments of basic education, since the subject is still very restricted to the technical and academic means. For these reasons, this article aims to propose geoeducational actions for the dissemination and valorization of geodiversity and geopatrimony in primary schools of Piauí, thus fostering their geoconservation. Based on a theoretical review on the topics addressed, six actions are suggested in this study: i) mini-courses for teachers; ii) lectures for students; iii) field classes with an emphasis on Geotourism; iv) identification of geosites; v) workshops for the production of dissemination and vi) use of games and fun with topics related to geodiversity and geopatrimony.
Keywords: Geodiversidade. Ações geoeducativas. Piauí.